Historical climate observations in Canada: 18th and 19th century daily temperature from the St. Lawrence Valley, Quebec. (10th April 2014) - Slonosky, Victoria
<x xml:space="preserve">Abstract</x> Daily observations of weather and climate for the province of Québec, Canada, start in the 18th century and continue to the present day. Daily temperature observations from 12 observers ranging from 1742 to 1873 are described here. The frequency distributions of the temperature observations from each of the historical weather journals are examined for data quality and consistency. Adjustments for differing types of exposures, particularly north wall exposures, are developed. It is shown that examination of the daily data distribution can be used to infer information concerning the instruments used and likely exposure in the absence of metadata. Comparisons of the relative frequency distributions of historical and modern hourly observations are used to assess the reliability of the daily historical temperature data, and are able to detect problems with instrument exposure or sampling biases. Historical observations of temperature from the 18th and 19th centuries are shown to be comparable to modern temperature data. These daily observations will be used in further studies to analyse changes in climate and extreme conditions on a decadal to centennial time frame, and will form part of international data sets for the reconstruction and analysis of past climate events.